The Effect of Tax Collection with Warning Letters and Distress Warrant on Individual Taxpayer Compliance (Empirical Study of KPP Pratama Sumedang District) - Kartika, Tita; Rohmawati, Siti; Adinegara, Ahmad Andi (Journal of Business, Accounting and Finance, 2024)
This study focuses on the Pratama tax service office located in Sumedang District for the period 2017-2021, which aims to determine how the effect of tax collection with a warning letter (X1) and a distress warrant (X2) on individual taxpayer compliance (Y). The method used in this research is quantitative method, with sampling using probability sampling method. The population in this study was 40,513 individual taxpayers who received warning letters and distress warrant and were registered at KPP Pratama Sumedang with a sample size of 100 individual taxpayers who received warning letters and distress warrant. Data analysis and hypothesis testing in this study using SPSS version 25. Based on the test results and hypotheses, it can be seen that tax collection with a warning letter (X1) has a significant effect on compliance of individual taxpayers with a Sig value. 0.000 and the test value is greater than table or 4.260 > 1.985. Furthermore, tax collection by distress warrant (X2) has a significant effect on Individual Taxpayer Compliance with a Sig value. 0.005 and the test value is greater than table or 2.871 > 1.985. Tax Collection with a warning letter and distress warrant has a significant effect together on Individual Taxpayer Compliance with the calculated F value is 37.433, while the significance is 0.000